Coherent polarization radiation of relativistic electrons in crystals - Morokhovskii, V.L. (Вопросы атомной науки и техники, 2014)
A brief narration about the history of those heated arguments and discussions around the nature of so-called parametric X-radiation, which were concluded by the recognition of the discovery the phenomenon of coherent polarization bremsstrahlung of relativistic charged particles in crystals. Some important information and comments, which stay over of notice of specialists till now are reported. Краткий рассказ об истории жарких споров и дискуссий вокруг природы так-называемого параметрического рентгеновского излучения, которые завершились признанием открытия явления когерентного поляризационного тормозного излучения релятивистских заряженных частиц в кристаллах. Изложены информация и комментарии, которые все еще находятся вне поля зрения специалистов. Коротка розповiдь про гарячi суперечки та дискусiї вiдносно природи так-званого параметричного рентгенiвського випромiнювання, якi завершилися визнанням вiдкриття явища когерентного поляризацiйного гальмового випромiнювання релятивiстських заряджених часток в кристалах. Викладенi iнформацiя та коментарi, якi все ще залишаються поза увагою спецiалiстiв.